DESCRIPTIVE STUDY ON CHALLENGES OF EMPLOYEES IN PUBLIC SECTOR OF ANDHRAPRADESH - RANI, Dr. T. SOBHA; PRATHIBA, L. (The journal of contemporary issues in business and government, 2021)
The present study is to evaluate the problems being faced by the women work force post bifurcation of the State of Andhra Pradesh. The study deals with the decisions, consequences, problems and the output of the political, economical and social changes in the State that have significant impact on Government Sector. The objective of the Study is to examine the problems of female employees working in Heads of Department of Government Sector (in State’s New capital Amaravathi), with a particular reference to pre and post bifurcation of the State of Andhra Pradesh. This study will be useful for the State Government, Officials to know the problems of employees of the State of Andhra Pradesh, who were forcefully migrated from the State of Telangana post bifurcation.